Migration chinoise et compétitions urbaines à Dakar - Guèye, Cina (De l'Orient à l'Occident, 2021)
At the crossroads of urban sociology and economic sociology, this book focuses on the competition unfolding in the urban space of Dakar between different categories of actors: groups of deterritorialized Chinese involved in trading activities, young local cobblers and street vendors. These actors of a globalization "from below", who discreetly shape the public space, upset the hierarchical order imposed by the wage society, by participating in the constitution of new economic and social hierarchies and new relationships of power. This research is also an invitation to go beyond the usual clichés regarding these local economic actors (referred to by the derogatory terms "baol-baol", "kaw-kaw") by focusing on the variety of their skills, the diversity of their backgrounds and their social and professional identities. This book is intended for social scientists interested in the forms of "non-hegemonic globalization" in the African context and in small-scale urban market production and its recent developments. Cina Guèye holds a doctorate in sociology from the University of Gaston Berger (Senegal) and the University of Lumière Lyon 2. She is a member of the CIERVAL laboratory (Centre interdisciplinaire d'études et de recherches de la vallée). Her research focuses on migration, labor markets, youth and gender.